Pembuatan Limbah Cangkang Melinjo Menjadi Briket Di Desa Pasir Waru Kecamatan Mancak - Achmad Syarifudin (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2019)
The aim of the Community Service Program “Kuliah Kerja Nyata” Skills Training is to improve the skills of the people of Desa Pasirwaru Kec. Mancak. The partners of this activity are the Melinjo emping craftsmen community in the village of Pasirwaru, Kec. Mancak. The problem faced is not knowing the use of melinjo shells to produce products that are useful and have a sale value. The method of implementing this service is through (1) Surveying through observation, interviews, and analysis of village problems and potentials, (2) Training on making briquettes from melinjo shells. The result of this program is to increase the community's knowledge and skills regarding the processing of melinjo shell waste into briquettes, this program is expected to facilitate the community in improving their knowledge and skills in treating existing waste.